STRATEGI PEMBERDAYAAN SUMBER DAYA MANUSIA UNTUK MENINGKATKAN PRODUKSI UMKM - Fitria Astuti; Siti Maryam; Burhanudin AY (ITB AAS Indonesia Surakarta, 2022)
The purpose of this study is to analyze the strategy of empowering human resources of weaving craftsmen at the center of the goyor sarong industry